2013
DOI: 10.5688/ajpe778175
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacogenetics Service Experience for Pharmacy Students, Residents, and Fellows

Abstract: Objective. To utilize a comprehensive, pharmacist-led warfarin pharmacogenetics service to provide pharmacy students, residents, and fellows with clinical and research experiences involving genotypeguided therapy. Design. First-year (P1) through fourth-year (P4) pharmacy students, pharmacy residents, and pharmacy fellows participated in a newly implemented warfarin pharmacogenetics service in a hospital setting. Students, residents, and fellows provided genotype-guided dosing recommendations as part of clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…However, study carried out in Malaysia, have discovered that current healthcare practitioners have good knowledge, attitude and consider PG to be a relevant field of clinical practice, but with low adoption (Bannur et al, 2014), and other studies have demonstrated healthcare students agree that PG is critical to patient care (Drozda et al, 2013;Gurwitz et al, 2005;McCullough et al, 2011;Moen and Lamba, 2013). Although about half of the participants have never attended lectures related to PG, a good knowledge and attitude was reported, and this could be related to advancement in technology and social media or News feeds especially when the President Barack Obama of USA talked about precision Medical at the White House to the media (The White House, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, study carried out in Malaysia, have discovered that current healthcare practitioners have good knowledge, attitude and consider PG to be a relevant field of clinical practice, but with low adoption (Bannur et al, 2014), and other studies have demonstrated healthcare students agree that PG is critical to patient care (Drozda et al, 2013;Gurwitz et al, 2005;McCullough et al, 2011;Moen and Lamba, 2013). Although about half of the participants have never attended lectures related to PG, a good knowledge and attitude was reported, and this could be related to advancement in technology and social media or News feeds especially when the President Barack Obama of USA talked about precision Medical at the White House to the media (The White House, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Weitzel and colleagues listed the different factors that affect educational approaches, such as class size and type of curriculum. 30 Educational approaches include didactic lectures, 31 clinical exercises and online resources, 32 personal genomic sequencing, 33 laboratory exercises 34 and bionformatics, 35 flipping content, 36 shortanswer problem solving, 31 medical literature review, 31 experiential activities, 37 and medical evidence review, among others. Some pharmacy schools have tried implementing students' personal genetic sequencing, 33 but this approach could be controversial, 38 and risks failing the four pillars of genetic counseling (autonomy, confidentiality, beneficence, and justice).…”
Section: (89) 7 (11)mentioning
confidence: 99%
“…To equip student pharmacists with the needed training, it is important that experiential learning opportunities are clinically robust in practice and student activities. 6, 43, 44 Practice-based experiences that incorporate pharmacogenomics can occur in IPPEs or APPEs. Given the complex nature of pharmacogenomics and its integration with other therapeutics topics, though, it most likely fits best during APPE training.…”
Section: Educational Approaches and Strategiesmentioning
confidence: 99%